(untitled) (Journal of Educational Sciences, 2022)
The article describes the media communication competencies that a future journalist develops in the educational system of the Bologna Process. It is known that a foreign language is taught as a compulsory component of higher education, according to which a future journalist develops the skills of communicating with foreign media related to his specialty. Although this competence is not transferred through special theoretical knowledge of a foreign language, we believe that it is formed on the basis of topics in educational materials, dictionaries, translation dictionaries, semantic materials, journalistic materials provided through reading and writing. At the same time, students of any specialty receive a foreign language education, respectively, if students acquire knowledge in a foreign language in accordance with their professional direction, their level of competence rises. Foreign language media communication competence is also very important in the double degree system in the modern educational system. In this case, the future specialist will learn not only about foreign media, but also about the mentality. For this reason, the level of competencies formed in foreign language education should be high. The article examines and analyzes 8 types of media competencies, in which the process of forming foreign media and communicative competencies of future journalists in the system of professional education is considered. We would also like to emphasize the need to develop legal competencies in addition to those recognized in science. Because in the professional activity of a journalist there are situations that are possible in the organization and broadcasting, but prohibited at the legislative level. Therefore, in addition to basic professional competencies, future professionals should also have legal competencies. Keywords: journalism, media and communicative competence, foreign language education, media literacy, legal competence, education system.